2018
DOI: 10.1002/dta.2492
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem tissue distribution of morphine and its metabolites in a series of heroin‐related deaths

Abstract: The abuse of heroin (diamorphine) and heroin-related deaths are increasing around the world. The interpretation of the toxicological results from suspected heroin-related deaths is notoriously difficult, especially in cases where there may be limited samples. To help forensic practitioners with heroin interpretation, we determined the concentration of morphine (M), morphine-3-glucuronide (M3G), and morphine-6-glucuronide (M6G) in blood (femoral and cardiac), brain (thalamus), liver (deep right lobe), bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Interest is currently focused on the quantification of drugs in PM materials other than blood, including bile, brain, liver, muscle, and vitreous humor . However, while these alternative materials show promising results with individual drugs or in specific circumstances, femoral venous blood still represents the most viable material for interpretative purposes in PM toxicology, with a more extensive range of reference concentrations published in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Interest is currently focused on the quantification of drugs in PM materials other than blood, including bile, brain, liver, muscle, and vitreous humor . However, while these alternative materials show promising results with individual drugs or in specific circumstances, femoral venous blood still represents the most viable material for interpretative purposes in PM toxicology, with a more extensive range of reference concentrations published in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, their extraction recovery was better than 70.0%. Other reported methods have measured total morphine after converting glucuronide conjugates of morphine to their free form with enzymatic hydrolysis (15,23) or have used direct determination of morphine and its glucuronide conjugates without hydrolysis using LC-MS-MS (24). In fact, few studies have reported the level of heroin metabolites in solid tissue specimens.…”
mentioning
confidence: 99%
“…However, the method was not applied to real liver specimens collected from postmortem cases. To the author's knowledge, only one method has been reported for analyzing postmortem liver tissues with LC-MS-MS (24). In that method, liver concentrations were determined using calibration curves derived from plasma extraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are too many confounding factors, for example, bone irroration, chemical properties of the drug, individual tolerance and metabolism, etc. [1,3,6,9,13,16,23,26,46,49‐51 ] whose mechanisms are beyond the scope of this study.…”
Section: Resultsmentioning
confidence: 99%